Advanced radiation techniques in the treatment of esthesioneuroblastoma: a 7-year single-institution’s clinical experience - Liermann, Jakob; Syed, Mustafa; Held, Thomas; Bernhardt, Denise; Plinkert, Peter K.; Jungk, Christine; Unterberg, Andreas; Rieken, Stefan; Debus, Jürgen; Herfarth, Klaus; Adeberg, Sebastian (Cancers, 2018)
(1) Background: Esthesioneuroblastoma (ENB) is a rare tumor entity originating from the olfactory neuroepithelium. There is a scarcity of data about different treatment strategies. Intensity modulated radiotherapy (IMRT) and carbon ion radiotherapy (CIRT) are advanced radiation techniques that might improve local tumor control. (2) Methods: This retrospective analysis contained 17 patients with ENB (Kadish stage ≥ C: 88%; n = 15). Four patients had already undergone previous radiotherapy (RT). The treatment consisted of either IMRT (n = 5), CIRT (n = 4) or a combination of both techniques (n = 8). Median follow-up was 29 months. (3) Results: In patients that had not been irradiated before (n = 13), calculated overall survival (OS) and progression free survival (PFS) rates after 48 months were 100% and 81% respectively (Kaplan-Meier estimates). Two of four patients that underwent reirradiation died after RT, presumably due to tumor progression. Besides common toxicities, five patients (30%) showed mostly asymptomatic radiation-induced brain changes, most likely due to a disturbance of the blood-brain barrier. (4) Conclusions: Our results demonstrate that IMRT, CIRT, a combined approach of IMRT and CIRT as well as reirradiation with CIRT seem to be feasible and effective treatment methods in ENB.